Semantics of Categoricals In Port-Royal Logic - Šopauskas, Laisvūnas (Problemos, 2004)
In this article, the author analyses semantics of categorical sentences presented by Antoine Arnauld and Pierre Nicole in their famous Logic or the Art of Thinking, known also as Port-Royal Logic. Their semantics of categoricals is analysed in three aspects: understanding of syntax, interpretation of elementary parts and dependence on context. The author comes to the conclusion that Arnauld and Nicole adhered to the variants of medieval semantic theories – inherence theory of categorical proposition and identity theory of categorical proposition. Parts of categoricals – copula and predicate – are interpreted differently in these theories. Also dependence of the meaning of sentence on the context is understood differently here. This leads the author to the conclusion that the combination of inherence and identity theories by Arnauld and Nicole was eclectic one. Also recent interpretations of Arnauld’s and Nicole’s semantics of categoricals, presented by Jean-Claude Pariente and Jill Vance Buroker, are evaluated. In the light of the results of this investigation interpretations of Pariente and Buroker are both considered as one-sided, but compatible.